‘Metema became my Istanbul’ : The Complex Transit Trajectories of Ethiopian Female Migrants - Zeleke, Meron (African Human Mobility Review, 2022)
Discussions on transit migration have for long focused on presenting the experiences of migrants transiting through a given place at a specific time in a linear manner. Accordingly, most prior researches adopt a snapshot approach to examine the lived experience of transit migrants. This paper argues that such an approach fails to aptly capture the gist of the complex nature of transiting and the dynamics of change in the migration trajectories. It emphasizes the need to have a diachronic approach in examining transit migration trajectory of migrants considering the fact that transit experience is not often bound to a given place and space as it can be inferred from the case of Ethiopian female migrants presented in this paper. Furthermore, the discourse on transit migration often portrays transit migrants as individuals stranded in a place against their will and lacking the agency to decide about their prospects of mobility/immobility. By drawing on an extended ethnographic study conducted over the course of five years (2017-2021) in Djibouti and in Ethiopia, this paper explores the intricate transit experiences of Ethiopian female migrants in two different transit places and their agency in deciding about their mobility/immobility, redefining their destinations and transit pathways, and settlement, a theme that escaped attention in prior works on female migration from Ethiopia.